Gendered Masculinity: An Analysis of Corso’s Marriage (Philologia, 2021)
“Beat Generation” is a term that refers to the writers and poets of the American society of 1950s. The “Beat” culture was both the outcome as well as the harbinger of a set of the literal, cultural, political, social and intellectual phenomenon that occurred in the 1950s and continued, in a metaphosed form, into the 60s. What formed the ‘The Beat Generation’ movement was in fact the distinctive reaction that individual artists and poets demonstrated, albeit separately, on different terms. One of the best depictions of the effect of such social conformity and restriction can be found in Gregory Corso’s poem “Marriage”. In this poem, a satiric vision of the hackneyed structures of conservatism and traditions prevalent in American society has been delivered. This paper aims at tracing the effects of performative gender-specific practices and norms in America of the 1950s and its impact on the formation of the Beat Generation revolt against those norms and “facts”. The research has been carried out on the basis of the gender theories of judith Butler, an American theoretician in feminist field as well as in gender studies. The researcher aims to demonstrate the effects of the conservative orthodox American society of Corso’s time, typically Beat generation period, on the masculine gender formation.
Keywords: Gregory Corso; Judith Butler; Gender Formation; Masculinity; Marriage